Oxidative Status in Adult Anorexia Nervosa Patients and Healthy Controls-Results from a Cross-Sectional Pilot Study - Jolana Wagner-Skacel; Fiona Haidacher; Markus Wiener; Karoline Pahsini; Sabine Marinschek; Theresa Lahousen; Willibald Wonisch; Susanne Bengesser; Mary I. Butler; Sonja Lackner; Andreas Meinitzer; Dietmar Enko; et al. (MDPI AG, 2022)
Oxidative stress describes an imbalance of reactive oxygen species (ROS) and antioxidative defence systems. Recently, the consequences of oxidative stress have become a central field of research and have been linked to the genesis of multiple psychiatric diseases. Some oxidative stress parameters have not been investigated before in anorexia nervosa (AN) patients, including the gut microbiota-derived metabolite trimethylamine N-oxide (TMAO) and polyphenols (PPm). In this cross-sectional pilot study, we evaluated these markers together with total peroxides (TOC), antioxidative capacity (TAC), endogenous peroxidase activity (EPA) and antibodies against oxidized LDL (oLAb) in serum samples of 20 patients with AN compared to 20 healthy controls. The antioxidative capacity was significantly decreased in AN patients, with a mean TAC of 1.57 mmol/L (SD: ±0.62); t (34) = −2.181, p = 0.036) compared to HC (mean = 1.91 mmol/L (SD: ±0.56), while the other investigated parameters were not significantly different between the two groups. In AN patients, TAC correlated with EPA (rsp = −0.630, p = 0.009). This study suggests that there is an antioxidative deficiency in AN patients. In this respect, there is a demand for interventional studies to determine whether antioxidants can be used as add-on therapy in the treatment of AN.